(untitled) (Bangladesh Journal of Botany, 2023)
It is well known that salicylic acid (SA) can help plants tolerate abiotic stresses. Nevertheless, the regulatory functions of SA in plants, such as the response of Fritillaria hupehensis Hsiao et K.C.Hsia to exogenous SA rational application under heavy metal stress, remain unknown. This study aimed to assess the relief effects of SA on the damage of F. hupehensis caused by heavy metal cadmium (Cd), as measured by physiological and biochemical characteristics. The results showed that bulb germination and seedling growth of F. hupehensis Hsiao et k. c. Hsia decreased under different Cd toxicity treatments. The radicle length and mitotic index also significantly decreased under Cd stress (P < 0.05), especially under high concentrations of Cd stress. The bulb germination and seedling growth increased slightly under medium concentration treatment compared to low concentration treatment. Cd toxicity treatment significantly reduced the contents of pigment, protein, and sugar in seedlings compared with the control. The contents of total antioxidants and malondialdehyde in Cd-poisoned seedlings increased significantly. The comprehensive treatment promoted the growth of bulbs and seedlings. As a result of Cd stress, SA application significantly increased the bulb germination rate, radicle length, mitotic index, pigment, protein, and sugar content. Lipid peroxidation and total antioxidants were decreased by comprehensive treatments compared with Cd toxicity treatment. This simple study remarkably broadened our understanding of the application and protection of SA in Cd stress. Bangladesh J. Bot. 52(2): 601-606, 2023 (June) Special